OSH in the school curriculum : requirements and activities in the EU Member States (Luxembourg, 2009)
"To underpin occupational safety and health (OSH) education in schools and colleges it is necessary to formalise it in curriculum requirements. This report reviews how the Member States are including OSH and risk education in their national curricula. The report shows that there is considerable progress and activity in this respect at both primary and secondary education levels in terms of both implemented and planned actions in the Member States. The report also identifies some success factors for mainstreaming OSH into education curricula."